Characterizing the Impact of Alfvén Wave Forcing in Interplanetary Space on the Distribution of Near-Earth Solar Wind Speeds - B. L. Alterman (The Astrophysical Journal Letters)
Broadly, solar wind source regions can be classified by their magnetic topology as intermittently and continuously open to the heliosphere. Early models of solar wind acceleration do not account for the fastest, nontransient solar wind speeds observed near-Earth, and energy must be deposited into the solar wind after it leaves the Sun. Alfvén wave energy deposition and thermal pressure gradients are likely candidates, and the relative contribution of each acceleration mechanism likely depends on the source region. Although solar wind speed is a rough proxy for solar wind source region, it cannot unambiguously identify source region topology. Using near-Sun observations of the solar wind’s kinetic energy flux, we predict the expected kinetic energy flux near Earth. This predicted kinetic energy flux corresponds to the range of solar wind speeds observed in the fast solar wind and we infer that the solar wind’s near-Sun kinetic energy flux is sufficient to predict the distribution of the fastest, nontransient speeds observed near Earth. Applying a recently developed model of solar wind evolution in the inner heliosphere, we suggest that the acceleration required to generate this distribution of the fastest, nontransient speeds is likely due to the continuous deposition of energy by Alfvén wave forcing during the solar wind’s propagation through interplanetary space. We infer that the solar wind’s Alfvénicity can statistically map near-Earth observations to their source regions because the Alfvén wave forcing that the solar wind experiences in transit is a consequence of the source region topology.